(untitled) (Research, Society and Development, 2020)
P-methoxycinnamic diesters from carnauba wax powder (PCO - C) – cinnamic acid derivate – have been associated with new properties such as hypolipidemic, hypocholesterolemic and hypoglycaemic effects in mice. The present study aimed to investigate the safety profile of PCO - C by evaluating the subchronic oral toxicity, genotoxicity and mutagenicity using in vivo experimental models. Therefore, for the present research, characterized as experimental and of a quantitative nature, 80 Swiss mice, of both genders, were used for the analysis of mutagenicity, genotoxicity, analysis of the biochemical, hematological and toxicological profiles. PCO - C did not induce changes in the mass of animals besides not interfering in blood parameters. PCO - C showed no hemolysis of mouse erythrocytes. PCO - C caused no mutagenic or genotoxic effects in male and female mice treated with 500 mg/Kg/day during 90 days. In addition, PCO - C did not change some important serum parameters (alanine aminotransferase, aspartate aminotransferase, total cholesterol and creatinine), hematological profile, structural arrangement of the kidneys, heart, stomach and spleen. The results demonstrate that PCO - C is not genotoxic, and did not present toxicity when used orally for up to 90 days. Overall, the study has demonstrated the safety of PCO - C for potential uses in biomedical areas.